Kebebasan Berkontrak Dan Prinsip Keadilan Perjanjian Leasing Dalam Perspektif Hukum Perdata - Kharisma, Buyung; Hayatuddin, Khalisah; Tanzili, Mulyadi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This study aims to analyze leasing agreements from a civil law perspective, focusing on the application of the principle of freedom of contract and the principle of justice. As an innominate agreement, leasing is generally set out in standard clauses determined unilaterally by the financing company, thereby creating an imbalance in the legal position between the lessor and the lessee. Although normatively valid under Article 1338 of the Civil Code, the practice of such contracts does not always reflect fairness, as they often contain unilateral clauses that are detrimental to the lessee. Using normative juridical methods and qualitative analysis, this study shows that the principle of freedom of contract must be interpreted in a limited manner and corrected by the principles of fairness, propriety, and protection of the weaker party. Therefore, modern civil law needs to be oriented not only towards formal legality, but also towards substantive justice that is capable of balancing the rights and obligations of the parties in a leasing agreement.